Polycyclic aromatic hydrocarbons (PAHs) in blood serum of adults living in high and low-traffic volume areas in Malaysia: A comparative cross-sectional study - Al-Battawi, Samer; Latif, Mohd Talib; How, Vivien; Thilakavathy, Karuppiah; Abd Hamid, Haris Hafizal; Hameed, Sarah; Ho, Yu Bin (Academic Press, 2024)
Ambient polycyclic aromatic hydrocarbons (PAHs) originate predominantly from fuel combustion of motor vehicles and have the potential to affect human health. However, there is insufficient knowledge regarding serum PAHs health risks among the Malaysian population. This study aims to compare PAH concentrations, distributions, correlations, and health risks in 202 blood serum samples drawn from residents living in high-traffic volume areas (Kuala Lumpur) and low-traffic volume areas (Hulu Langat) in Malaysia. Solid phase extraction and gas chromatography-mass spectrometry (GC-MS) were employed to extract and analyze blood serum samples. Questionnaires were distributed to obtain sociodemographic and contributing factors of serum PAHs. The mean total PAHs concentration in serum of the Kuala Lumpur group was 54.44 ng g−1 lipids, double the Hulu Langat group's concentration (25.7 ng g−1 lipids). Indeno(1,2,3-cd)pyrene (IcP) and acenaphthene (ACP) feature the most and least abundant compounds in both study groups. The mean concentrations of IcP and ACP in the Kuala Lumpur and Hulu Langat groups were 26.8 vs 12.68 and 0.27 vs 0.14 ng g−1 lipids, respectively. High-molecular-weight PAHs (HMW-PAHs) composed 85% of serum total PAHs in both groups. Significant correlations were found (i) between the individual serum PAH congeners (p < 0.01) and (ii) between serum PAHs and total lipids (p < 0.01). According to the questionnaire data, high traffic volume and outdoor hobbies were the only contributory factors that confirmed significant relationships with serum PAHs (p < 0.001). Health risk assessment was computed using benzo(a)pyrene (BaP) equivalent (BaPeq) and demonstrated that the Kuala Lumpur group has twofold greater carcinogenic risk than the Hulu Langat group (16.11 vs 7.76 ng g−1 lipids). Our study reveals that traffic volumes notably impact serum PAH levels and general health among the Malaysian population. © 2024 Elsevier Inc.